(3bHS GdCfhGQs - (3eLO GdOjf ESeGYjd Hf EHQGgje Hf eMeO GdHdHjSis; (3YHO Gddg Hf Ydj Hf YHO Gddg GddNej GdCfOdSj, CHh eMeO , GdQTGWj,J (B542 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg HJQLeI GdHGHdJi s
(3BNQgG (B:s
(3hjfJgi HJQLeI Gddjfi s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B105 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B262s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B320 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs